Abandono familiar y la salud mental de los adultos mayores del centro gerontológico de Quevedo - Pincay Herrera, Delia Elizabeth (2018)
When reaching the third age, people find themselves facing a new reality, the roles are changing, the family makes the most important decisions, and at the same time must take care of the manager, who, in many cases, is seen as a "burden", not annoyance within the home. When the family does not want to take care of the old man, opts for the abandonment of the most cruel forms, throwing them out of the house or in other cases leaving them in a gerontological center, breaking any communication or affective ties with the elderly. This work focuses on the mental health of the elderly and the abandonment of the family of the Quevedo Gerontological Center; exposing its consequences that are reflected in low self-esteem, depression, anxiety, and other negative feelings, as well as affecting their physical health by the loss when receiving the medication. It has been proposed as a proposal to improve the mental health of older adults, the development of a psychotherapeutic guide, in a personalized way, as a couple and as a group, becoming a contribution to the institution and to society, breaking the paradigms that discriminate against people older adults, adhering to the rights of vulnerable people to the standards of Good Living.